(untitled) (Experimental biology, 2009)
By the thin-layer chromatography on silicagel it was identified, that milk of C. bactrianus, C. dromedarius and hybrids contains phospholipids, sterols, free fatty acids and triacilglicerols. In the process of fermentation and transformation of milk into shubat there are formed the new fractions near sterols and phospholipids.